2009
DOI: 10.1016/j.molimm.2009.07.001
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DM mediates peptide exchange by interacting transiently and repeatedly with HLA-DR1

Abstract: The peptide editor HLA-DM (DM) catalyzes the exchange of peptides bound to MHC class II molecules within antigen presenting cells by generating a “peptide-receptive” MHC class II conformation (MHCreceptive) to which peptides readily bind and rapidly unbind. While recent work has uncovered the determinants of DM recognition and effector functions, the nature of MHCreceptive and its interaction with DM remains unclear. Here, we show that DM induces but does not stabilize MHCreceptive in the absence of peptides. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 33 publications
1
30
0
Order By: Relevance
“…DM binds MHC II near the N-terminus of the peptide binding groove and disrupts peptide binding by inducing or stabilizing a conformation with altered alpha subunit 3 10 helix and adjacent extended strand (21, 28, 36). The region with altered structure is involved in key MHC II-peptide interactions (21, 32, 35). MHC II-peptide complexes appear to be highly dynamic and adopt various conformations (40, 41).…”
Section: Introductionmentioning
confidence: 99%
“…DM binds MHC II near the N-terminus of the peptide binding groove and disrupts peptide binding by inducing or stabilizing a conformation with altered alpha subunit 3 10 helix and adjacent extended strand (21, 28, 36). The region with altered structure is involved in key MHC II-peptide interactions (21, 32, 35). MHC II-peptide complexes appear to be highly dynamic and adopt various conformations (40, 41).…”
Section: Introductionmentioning
confidence: 99%
“…The strong interactions within and between HLA-DQ and DR loci in B cells (Fig 6A) are consistent with this core component (antigen-presentation in thymic APCs) of T1D phenotype, and supports our earlier conclusion that thymic B cells are among the major components of the APC repertoire. The HLA-DM gene encodes a chaperone that facilitates the loading of peptides in the late endosome within this antigen presentation pathway [31, 36] (Fig 4C); hence, the interaction of the DM-proximal region with HLA-DQ and DR .…”
Section: Resultsmentioning
confidence: 99%
“…In Fig 7, the high association of MHC class II antigen presentation , represented by the class II genes including HLA-DM and HLA-DO , reflects the general dominance of HLA-DQ and HLA-DR loci in Fig 2: MHC class II molecules assembled in the ER with the invariant chain (Ii), initially occupying the peptide binding domain, moves into an endosomal compartment and Ii is exchanged with antigenic peptides with the help of HLA-DM and HLA-DO, which down-regulates HLA-DM in B cells [31, 36, 46]. The peptide-MHC class II complex is then displayed on the plasma membrane (Fig 4C).…”
Section: Resultsmentioning
confidence: 99%
“…To generate peptides with increased DM-susceptibility, we substituted the P1 pocket residue of A2 104–117 from tryptophan to isoleucine (W1I) or to threonine (W1T), because the P1 pocket residue is one of the major anchor residues (Murthy and Stern, 1997; Stern et al, 1994) and has been implicated in determining DM-susceptibility (Anders et al, 2011; Narayan et al, 2009; Pos et al, 2012; Schulze and Wucherpfennig, 2012; Yin and Stern, 2013). As expected, A2 104–117 , W1I and W1T all showed a concentration-dependent inhibition on the binding of probe peptide Alexa488-HA 306–318 to DR1, with A2 104–117 having the highest affinity and W1T the lowest (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, it has been demonstrated that MHCII molecules undergo a reversible isomerization between peptide-receptive and peptide-averse states, and DM may catalyze peptide association by accelerating the transition of peptide-averse to peptide-receptive conformation, or stabilizing the peptide-receptive form (Grotenbreg et al, 2007; Natarajan et al, 1999; Rabinowitz et al, 1998). Moreover, multiple intermediates formed between peptide, MHCII and DM during peptide association, dissociation and exchange have been proposed although the detailed mechanisms are still in debate (Anders et al, 2011; Ferrante et al, 2008; Grotenbreg et al, 2007; Narayan et al, 2009; Pashine et al, 2003; Pos et al, 2012; Zarutskie et al, 2001). It is possible that reaction steps not included in our simulation reaction scheme might put some constraints on the interpretation on the IC 50 data.…”
Section: Discussionmentioning
confidence: 99%